Population Growth and Economic Growth Performance in Nigeria (1981 – 2014) - ESSIEN, Ettah Bassey (Turkish Economic Review, 2016)
Abstract. There has been intense debate in the literature on the role of population growth in economic growth performance. Some scholars believe that increases in the population of a nation tantamount to economic progress, others see population increase as a curse rather than a blessing, but a few scholars also believe that population assumes a neutral position in economic growth process. This paper therefore sought to assess the role of population growth in economic growth performance in Nigeria. The study employed time series data for the period 1981-2013. Using Augmented Cobb-Douglass Production Function (gleaning from Solow Growth Model), and relying on error correction modelling framework, the econometric results established the fact that population growth has the potentials of fostering economic growth in Nigeria, but underlined the fact that this and other benefits would depend on, not only the chunk of the entire population that is active, but the quality of the population. Amongst other policy options suggested, it was advocated that policy measures that will foster target-oriented and skill-enhancing education and training should be designed and implemented. Provision of accessible and affordable healthcare for a healthy population was also advocated if Nigeria’s population growth must be advantageous. Keywords. Population Growth, Economic Growth, Human Capital Development, Cointegration, ECM. JEL. C32, H5, N3.